Pre-operative serum albumin and body mass index as predictors of post-operative morbidity and mortality in perforation peritonitis secondary to peptic ulcer disease - K. R., Bhanu Prakash; Mohan, Manasa; Patil, Subhas (International Surgery Journal, 2021)
Background: Peptic ulcer disease (PUD) affects 4 million people worldwide annually. Perforated peptic ulcer is a serious complication of PUD and patients often present with acute abdomen that carries high risk for morbidity and mortality. This is worsened in patients who are malnourished. The incidence of malnutrition is around 30% in patients with gastrointestinal disease and is frequently unrecognized. Albumin or prealbumin levels may help identify these patients. Obesity is also another cause for morbidity and has deleterious effects on wound healing. Therefore this study was carried out to assess if preoperative serum albumin and body mass index can be used as predictors of morbidity and mortality in patients with perforated peptic ulcers. Methods: 70 patients with peptic perforation peritonitis presented to the hospitals attached to Bangalore Medical College and Research Institute from November 2018 to May 2020 and were included in the study. Pre-operative Serum Albumin and BMI was noted and the patients were followed up for 30 days. Results: Mean albumin level in our study was 3.01. The patients with Serum Albumin <3.5 g/dl have more complications compared to patients with >3.5 g/dl. Morbidity and mortality increases with severity of hypoalbuminemia. This study was statistically significant with a p value <0.05. In our study, we also found that patients with abnormal BMI have more complications than patients with normal BMI but it is statistically insignificant with a p value >0.05. Conclusions: Serum albumin is a good indicator for predicting postoperative morbidity and mortality in peritonitis secondary to peptic ulcer disease.